Optimizing the Investigation of the General Crime Unit of the Pemalang Police Criminal Investigation Department in the Context of Solving Gambling Cases - Ash-shiddiq, Abdul Aziz (Advances in Police Science Research Journal, 2024)
Gambling is a criminal offense that has existed since the Dutch colonial era. Gambling itself is any form of game that involves money as a bet. Gambling has many forms ranging from traditional ones such as dice gambling, card gambling, togel gambling (toto gelap), to modern ones that use online media. Gambling itself has been rampant in various parts of Indonesia, especially in Pemalang district. Since 2019, gambling cases in Pemalang have had an imperfect settlement rate. This is due to the fact that the investigation of the General Crime unit of the Pemalang Police Criminal Investigation Department has not been optimized for the settlement of gambling cases. This research describes the organizational resources owned by the General Crime unit as well as the systems and methods used in the settlement. The author uses a qualitative approach in this research. This study uses management theory, SWOT theory, and competency theory as an analytical knife to solve the problems that have been formulated. This research aims to find out the description of the technical and tactical settlement of gambling cases carried out by the General Crime Unit of the Pemalang Police Criminal Investigation Department. The findings of this study are the lack of General Crime unit personnel, there are still members of the General Crime unit who have not carried out development education, and there is still backing by Polri personnel. The conclusions drawn are in the form of asking for cross-sectoral assistance, sharing information for members who have already carried out vocational education, and conducting postal checks on General Crime unit personnel who are suspected of backing up gambling actors. The author hopes that the results of this research can be used as input for Pemalang Police to be better in the future and can be used as a reference for other writers.